The applicability of the “Sniffin’ Sticks” olfactory test in a Turkish population - Kendirli, Mustafa Tansel (Medical science monitor, 2013)
Olfactory assessment is often neglected in clinical practice, although olfactory loss can assist in diagnosis and may lead to significant morbidity. "Sniffin' Sticks" is a modern test of nasal chemosensory performance that was developed in Germany and validated in many countries. Our aim was to validate the applicability of "Sniffin' Sticks" in a Turkish population. The study included 123 healthy volunteers with a reported normal sense of smell and 51 patients complaining of a reduction in their olfactory function presenting either at rhinology or neurology clinics. The mean age of the subjects tested was 30.2±12.5 years in 126 males and 48 females. The participants were divided into 2 groups according to subjective olfactory function - healthy or abnormal. Each subject's olfactory function was assessed using the "Sniffin' Sticks" test. We found significant differences in "Sniffin' Sticks" test results between the abnormal and healthy groups. In healthy subjects, the 10th percentiles of odor threshold score, odor discrimination score, odor identification score, and TDI score were 7.25, 12, 11, and 32, respectively. Considering the 2 groups together, apple and turpentine were the least well-recognized odors from the 16 odors presented. Our study provides an update of normative values for routine clinical use of "Sniffin' Sticks" in a Turkish population. Also, the present study validates that "Sniffin' Sticks" olfactory test was applicable for clinical usage in a Turkish population.